1977
DOI: 10.1002/cber.19771100631
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Chemie der Halogensilan‐Addukte, XI. Bis(1,10‐phenanthrolin)‐Komplexe des Siliciums. Darstellung, Struktur und Eigenschaften

Abstract: Their solvolytic stabilities are similar to those of the corresponding bidbipyridine) complexes.They are dependant on the substituents X and Y. These properties may be related to the relative acceptor strength of the silanes. Steric factors appear to be of little importance. I. r., 'H n. m. r., u. v. spectra, and reactions are reported. Bis(2,2'-bipyridin)Komplexe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It should be noted that our observed UV-Vis spectrum of [Si(phen) 2 (OMe) 2 ] I 2 in CH 3 OH is the same as the one reported by Kummer et al [8]. As one can see in Table V ϩ2 theory predicts a band at 557 nm which corresponds to a charge transfer band (CTB) from I to phenathroline ligand molecule according to analysis of molecular orbitals participating in this transition (Fig.…”
Section: Structure and Uv-vissupporting
confidence: 76%
See 2 more Smart Citations
“…It should be noted that our observed UV-Vis spectrum of [Si(phen) 2 (OMe) 2 ] I 2 in CH 3 OH is the same as the one reported by Kummer et al [8]. As one can see in Table V ϩ2 theory predicts a band at 557 nm which corresponds to a charge transfer band (CTB) from I to phenathroline ligand molecule according to analysis of molecular orbitals participating in this transition (Fig.…”
Section: Structure and Uv-vissupporting
confidence: 76%
“…2 The structures of all calculated hexacoordinate compounds had cis-octahedral conformation with C 2 symmetry [8,15]. Figure 1 [15].…”
Section: Calculation Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The general approach to bis-bipyridine or bis-phenanthroline hexacoordinate silicon complexes is is generated by the reaction of SiI4 with bipyridine or phenanthroline in dichloromethane or chloroform. [36,37] Even with excess ligand, the reaction does not proceed beyond bis-substitution.…”
Section: Complexes With Two Bipyridine or Phenanthroline Ligandsmentioning
confidence: 99%
“…Besides unique chemical features, 1 developments relating to new structural varieties of these silicates have also come to light. 2−5 Cationic complexes were known for a long time, 6 although the authors have demonstrated their use as precursors to hexacoordinate bicyclic silicate dianions. 7 The authors have reported earlier penta and hexacoordinate silicate anions with SiO 4 N and SiO 4 N 2 skeletons, respectively, where silicon-nitrogen linkage was derived from acyclic substituent(s).…”
Section: Introductionmentioning
confidence: 99%